Method of Calculation of Integrated Performance Indicators of Defense Industry Organizations - S. E. Eroshin (Статистика и экономика)
The purpose of the study is to develop a parametric monitoring system for defense industry enterprises, optimizing on the principle of minimum sufficiency a set of key indicators of the activities of organizations and increasing the efficiency of management of research institutes, design bureaus, industrial and service enterprises of the military-industrial complex.Materials and methods. The methodological and theoretical basis of the presented scientific work is a system of mathematical methods for analyzing empirical data on the object of study, providing objective, accurate and systematic information on the researched processes. The reliability of scientific provisions, conclusions and practical recommendations is confirmed by the experience of applying the results of the study in the analysis of the activities of enterprises of Concern Almaz-Antey JSC, as well as comparing them with the results of research by domestic and foreign scientists in the field of organizing a management system for high-tech companies. Author relied on actual statistical information about the activities of organizations of the military-industrial complex, the results of research in the field of mathematical analysis, organization and planning of machine-building production, research of operations, rank statistics, probability theory, theory of adaptive management, economics and enterprise management.Results. A method has been developed for processing data on the activities of enterprises and reducing them to the optimal set of observed indicators without losing awareness of the monitoring object; possibilities of using non-parametric methods of statistics for analysis of complex systems, in particular, holdings of defense industry, have been researched.Conclusion. Each enterprise has its own specificity depending on the specifics of the production processes. There is now a significant number of different indicators that comprehensively, and often too extensively, characterize what is happening. This situation often makes it difficult to manage production facilities, since the actual picture of the state of the facilities is obscured by an excess of secondary information. In this regard, it seems reasonable to try to weed out unnecessary indicators and use only those that carry the necessary amount of information sufficient to reflect the specifics of the enterprise. The presented work theoretically and practically proved the advantages of using non-parametric statistics in enterprise monitoring, which allows reducing temporary losses in the development of management solutions and increasing their efficiency at the level of the parent companies of defense-industrial associations.